O vir-a-ser sujeito: questões preliminares ao estudo das graves psicopatologias dainfância - Alice Oliveira Rezende (2017)
Abstract: The present dissertation aims to investigate some aspects of the subjective constitution from our hypothesis, based on the Lacanian perspective, of the acquisition of the child by language. We intended to clarify certain nuances of the clinic with children at subjectivation risk, generically named as severe infantile psychopathologies. By approaching the processes that engender the infans speech emissions, we discerned the first modes of testifying hers/his affectation by language. We searched for Freuds conception regarding the genesis of the relation between the neonate and language. We then verified that the father of psychoanalysis would allow us to suppose that, albeit submersed in the symbolic field, the infans does not initially dispose of a mental apparatus that would enable her/him to discretize, articulate and register the unities of language in conformity to the shared language. Inconsidering, with Lacan, that language is inoculated by the primordial Other, we perscrutated the logical moments of jouissance, angst and desire traversed by the child, from the transitivistic relation to the moments of extraction of the instinctual objects (objects a: oral, anal, gaze and voice). Still, we basted the specter of incidence of the lack of satisfaction constitutive of the subject: deprivation (real), frustration (imaginary) and castration (symbolic). We then supposed that, firstly, the subject would be apprehended by a sonorous block, privileged solely through a jouissance fruition, still without any communication function. Freud designated this inaugural functioning mode as pleasure of the nonsense, in which the assonance preponderates. It is the first intervention of language, established by Lacan through the term lalangue, pure nonsense. As original equivoque, lalangue will reverberate in all forms of saying, setting up the structural misunderstanding between thespeaking beings. Furthermore, the notion of holophrase was used by Lacan to designate the frozen signifiers stackings, that is, non-discretized signifiers. Lalangue and holophrase embrace childrens ways of verbalizing, which, despite still being located externally to speech, attest modes of language resonance in the body. Piercing or compressing the signifier chain, both these vocalizations reveal the symbolic extension in which the subject can transit. Lastly, one ponders that, by recognizing in our clinical operations the edges and fringes that testify the resonance of language in the subject, the object voice is at stake. We would, thus, find modalizations susceptible of unfolding some distance between language and subject, which is indispensable for the subject to be able to mediate, through language, the orientation of hers/his desire.